2020
DOI: 10.18574/nyu/9781479839216.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Digital City

Abstract: The Digital City focuses on the interface of people, urban place, and the role that digital media play in placemaking endeavors. Critics have understood digital media as forces that alienate and disembed users from space and place. This book argues that the exact opposite processes are observable: many different actors are consciously and habitually using digital technologies to re-embed themselves within urban space. Five case studies from cities around the world illustrate the concept of “re-placeing” by sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…One of the design specifications emerging from the first design sprint was thus the need for procedures for feeding the captured photos back to the participants in order to enable them to interpret the data. The choice also fits with more general findings by scholars like Halegoua (2020) and Manovich (2020) who have both shown that digital and visual media are a ubiquitous part of contemporary urban experience and how we build emotional attachments with(in) urban environments.…”
Section: The Urban Belonging Projectsupporting
confidence: 82%
“…One of the design specifications emerging from the first design sprint was thus the need for procedures for feeding the captured photos back to the participants in order to enable them to interpret the data. The choice also fits with more general findings by scholars like Halegoua (2020) and Manovich (2020) who have both shown that digital and visual media are a ubiquitous part of contemporary urban experience and how we build emotional attachments with(in) urban environments.…”
Section: The Urban Belonging Projectsupporting
confidence: 82%
“…Through growing and competing uses of location-aware mobile technologies, geographic places gain new meanings based on the information attached to them (de Souze e Silva & Frith, 2012). Wilken (2019) argues that the increasing embeddedness of geolocation into devices and apps has led to a "democratization of locative media" that fundamentally reshapes "everyday engagements with location, communication, and social interaction" (p. 7), and Halegoua (2019) points out that the geocoding of images enables people to make claims about the meaning of place to audiences beyond their own social networks. As Molnár (2017) argues, before the diffusion of smartphones with integrated cameras, and digital media platforms with networked infrastructure that enabled the dissemination of images, the impermanence of street art meant people had to be in a certain place at a certain time to discover the work.…”
Section: The Social Media Citymentioning
confidence: 99%
“…Along the same lines, emphasized the transnational and cosmopolitan life of modern migrants in the digital age. More recently, a growing body of literature is examining the life of mobile and transient migrants (Gomes, 2017;Lee, 2020), and the concept of "digital place-making" (Halegoua, 2020;Halegoua & Polson, 2021;Hjorth, 2012;Wilken & Goggin, 2012;Fast et al, 2018), viewed as the "use of digital media to create a sense of place for oneself and/or others" (Halegoua & Polson, 2021, p. 574) within the context of mobility and migration. Other research has specifically examined social media usage and the making of place among mobile middleclass professionals (Polson, 2015;Kraemer, 2014;.…”
Section: Introductionmentioning
confidence: 99%